Impact of burn injuries on maternal and fetal outcomes during pregnancy: A prospective study at a tertiary care hospital - Pankaj Kumar Sarkar; Debashis Biswas; Sib Sankar Murmu; Riddhisundar Samanta (Asian Journal of Medical Sciences, 2025)
Background: Burn injuries are a significant public health concern in India, consuming substantial healthcare resources, with a higher prevalence in rural areas. The management of burns during pregnancy is particularly challenging due to limited published data, making treatment difficult in peripheral hospitals. Given this context, we conducted a retrospective analytical study on burn injuries in pregnant women. Aims and Objectives: This study aims to analyze the clinical presentation of pregnant burn patients and evaluate the impact of burns on maternal and fetal outcomes. Materials and Methods: A total of 33 pregnant women with burn injuries were analyzed. The study assessed the causes of burns, maternal mortality, and fetal complications. Results: Among 187 female burn patients of reproductive age admitted during the study period, 33 (17.6%) were pregnant. Of these, 27 had burns covering <50% of the total body surface area (TBSA), while 6 had burns exceeding 50% TBSA. Maternal mortality was lowest in cases with TBSA below 25% and significantly increased when TBSA exceeded 50%. Fetal mortality followed a similar pattern. Burn severity, shock, and respiratory complications were the primary determinants of maternal and fetal outcomes. Conclusion: Burn injuries during pregnancy have severe consequences for both maternal and fetal health. While early and aggressive management can mitigate some adverse effects, prevention remains the most effective strategy to reduce morbidity and mortality.